(untitled) (ILMIY TADQIQOTLAR VA YANGI OLAM, 2026)
ANNOTATION: This article examines the key factors of competitiveness in the implementation of global business strategies through an international market analysis, using Korzinka.uz as a case study. In the context of increasing globalization and digital transformation, companies operating in emerging markets face both new opportunities and significant challenges in achieving sustainable competitive advantage. The study focuses on analyzing market conditions, consumer behavior, competitive dynamics, and strategic positioning within the retail sector.